2016
DOI: 10.1007/s00464-016-4847-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of laparoscopic D2 lymphadenectomy with complete mesogastrium excision for advanced gastric cancer

Abstract: The anatomical boundary of mesogastrium is well described and dissected within D2 + CME surgical process. It proves to be safely feasible and repeatable with less blood lost, qualified lymph nodes retrieval results and other improved short-term surgical outcomes in advanced gastric cancer. Meanwhile, potential disseminated cancer cells fall into the mesogastrium can be eradicated by D2 + CME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…However, there is another less common procedure to treat gastric cancer. Although some surgeons have attempted D2 + complete mesogastrium excision (CME) or total gastrectomy through the outside bursa, the standard surgical plane and technique for CME are still unclear [11,12]. In contrast to the free part of the stomach, the posterior part of the stomach is composed of complex anatomical structures, including multiple fascias of the perigastric mesogastrium, intricate vascular networks and peripheral organs.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is another less common procedure to treat gastric cancer. Although some surgeons have attempted D2 + complete mesogastrium excision (CME) or total gastrectomy through the outside bursa, the standard surgical plane and technique for CME are still unclear [11,12]. In contrast to the free part of the stomach, the posterior part of the stomach is composed of complex anatomical structures, including multiple fascias of the perigastric mesogastrium, intricate vascular networks and peripheral organs.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, D2 + CME was associated with a lower rate of high CEA expression in the peritoneal fluid (15 per cent) and better DFS. A previous study found that mean(s.d.) intraoperative bleeding was 12·44(22·89) ml and duration of hospital stay was 11·09(4·28) days in patients undergoing laparoscopic distal gastrectomy with CME.…”
Section: Discussionmentioning
confidence: 97%
“…Patients in the D2 + CME group receive standardized LADG with D2 + CME [ 15 ], which is performed by the founder of this procedure. The standard D2 + CME procedure should meet the following criteria: Clearly exposing five mesogastrium (left gastroepiploic mesentery, right gastroepiploic mesentery, left gastric mesentery, right gastric mesentery, and postgastric mesentery) En bloc separation of the mesentery from the mesenteric bed Dissecting along the root of the mesentery Ligation should reach the root of the blood vessels.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have demonstrated the existence of disseminated cancer cells (named metastasis V) in the mesogastrium [ 12 , 13 ] that presented an understandable mesogastrium model for gastrectomy [ 14 ]. Therefore, we put forward D2 lymphadenectomy plus complete mesogastrium excision (D2 + CME) to resect both the primary lesion and adjacent tissue as completely as possible to avoid residual tumor or cancer cell spreading [ 15 ]. Although a retrospective study has shown that D2 + CME exhibited advantages in intraoperative hemorrhage and postoperative recovery course [ 15 ], there is still no prospective randomized controlled trial assessing its therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation